A comprehensive review on technological advances of adsorption for removing nitrate and phosphate from waste water. (October 2022) - Priya, E.; Kumar, Surendra; Verma, Chhavi; Sarkar, Sudipta; Maji, Pradip K.
Abstract: Nitrate and phosphate contamination in water sources is considered a major problem globally. The excessive discharge of nitrate and phosphate is responsible for the most widespread contamination in an aquatic system, causes eutrophication to harm the ecosystem, and severe threats to people's health. So the removal and recovery of these nitrate and phosphate are esteemed as one of the interventions to prevent the water bodies' eutrophication by application of numerous methods. Adsorption is a low-cost, efficient, environmentally friendly, and universal method utilized to remove nitrate and phosphate from wastewater. Here we review adsorption as an effective method for removing nitrate and phosphate from an aqueous solution, even with a low effluent concentration in the water medium. The major points are the following: first, this review compiles the data reported in the various literature about nitrate and phosphate removal through adsorption using different adsorbents like carbon base, clay base, zeolite base, chitosan, agricultural waste, cellulose nanocrystal, cellulose nanofibre, metal hydroxide, and biochar base. Second, the adsorption capacity, preparation, and modification method of adsorbents, the effect of temperature, and pH of using such adsorbents for removing nitrate and phosphate have also been discussed. Third, a discussion of some high-performance adsorbents for the removal of nitrate and phosphate is proposed; this is a key novelty of this review work. Moreover, the future outlook and upcoming nitrate and phosphate removal and recovery challenges are presented. Graphical abstract: Unlabelled Image Highlights: Removal of nitrate and phosphate using conventional methods has certain drawbacks. Adsorption is probably the key to effectively removing N and P from the environment. Major N and P removal is based on electrostatic and inner-sphere complex mechanisms. SO4 2−, HCO3 −, and Cl − are the most competitive ions for the adsorption of N and P. Nano-CS/Clino and CaO-biochar exhibit excellent N and P adsorption, respectively.